Methods of evaluating the force-velocity profile through the vertical jump in athletes: a systematic review - Contreras-Diaz, G.; Jerez-Mayorga, D.; Delgado-Floody, P.; Arias-Poblete, L. (Archivos de medicina del deporte, 2018)
Introduction: In the world of sport, the ability of humans to develop maximum muscular power (Pmax) is directly related to performance and sporting success. For this, the measurement of the force- velocity profile (F-v) plays a key role in the evaluation of the athlete. At present, there are different methodologies and technologies to assess this profile, with sprint and vertical jump being the most used forms. The objective of this review is to identify and analyze different methods and tools for assessing F-v profile through the vertical jump.